Electrochemical Cycling of Sodium‐Filled Silicon Clathrate. Issue 2 (23rd September 2013) - Wagner, Nicholas A.; Raghavan, Rahul; Zhao, Ran; Wei, Qun; Peng, Xihong; Chan, Candace K.
<x xml:space="preserve">Abstract</x> Be our guest! Silicon clathrate with sodium guest atoms is studied as a potential anode material for lithium‐ion batteries. An electrochemical, structural, and first‐principles analysis is conducted to understand the phase changes occurring upon lithium insertion and removal from these cage‐like silicon structures.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>